Breastfeeding to 12 mo and beyond: nutrition outcomes at 3 to 5 y of age. Issue 2 (7th August 2018) - Borkhoff, Cornelia M; Dai, David W H; Jairam, Jennifer A; Wong, Peter D; Cox, Kelly Anne; Maguire, Jonathon L; Birken, Catherine S; Macarthur, Colin; Parkin, Patricia C
ABSTRACT: Background: Little is known about nutrition outcomes in preschoolers associated with breastfeeding duration beyond 12 mo of age. Objective: The aim was to examine the association between total breastfeeding duration and nutrition outcomes at 3 to 5 y of age. Design: A cross-sectional study in healthy children, ages 3–5 y, recruited from 9 primary care practices in Toronto was conducted through the TARGet Kids! (The Applied Research Group for Kids) research network. Parents completed standardized surveys, including the Nutrition Screening for Every Preschooler (NutriSTEP) used to assess nutrition risk. Results: A total of 2987 children were included. Ninety-two percent of children were breastfed, and the mean ± SD breastfeeding duration was 11.4 ± 8.4 mo. The prevalence of nutrition risk (score >20) was 17.0%. We examined breastfeeding duration as a continuous variable. With the use of restricted cubic spline modeling, we confirmed a nonlinear relation between breastfeeding duration and NutriSTEP score, dietary intake and eating behavior subscores, and sugar-sweetened beverage and sweet-savory snack consumption. Segmented linear regression was used to examine this nonlinear relation in a piecewise approach. We found a decreasing trend in NutriSTEP score for children who were breastfed for 0–6 mo (β = −0.14; 95% CI: −0.29, 0.004), a significant decrease in NutriSTEP score for children breastfed for 6–12 mo (β = −0.20; 95% CI: −0.33, −0.07), and no significant change after 12 mo (β = 0.09; 95% CI: −0.07, 0.24) and beyond. The mean ± SD NutriSTEP scores were 17.1 ± 7.4 for no breastfeeding, 15.9 ± 6.5 for breastfeeding >0–6 mo, 13.9 ± 6.2 for >6–12 mo, 13.7 ± 6.3 for >12–18 mo, 14.6 ± 6.7 for >18–24 mo, and 14.3 ± 6.8 for >24–36 mo. Conclusions: Breastfeeding for ≤12 mo was associated with decreased nutrition risk and healthier eating behaviors and dietary intake at 3–5 y of age. We found insufficient evidence of additional benefit for breastfeeding beyond 12 mo of age. The TARGet Kids! practice-based research network is registered at www.clinicaltrials.gov as NCT01869530.